Nurses' perceptions of career ladder systems, job satisfaction and turnover intention: A cross‐sectional study - Young Seon Ahn; Jeong Sil Choi (Wiley, 2023)
Abstract Aim This study aimed to compare nurses' perceptions of career ladder systems, job satisfaction and turnover intention in small‐ and medium‐sized hospitals with and without a career ladder system. Design A cross‐sectional, correlational, descriptive study was conducted. Methods Data were collected using self‐report surveys from 130-144 participants in small‐ and medium‐sized hospitals with and without a career ladder system, respectively. The data were collected from July 1, 2019‐July 31, 2019. Results The perception of the career ladder system was positively correlated with job satisfaction in hospitals with and without a career ladder system but negatively correlated with turnover intention in those with a career ladder system only. A positive perception of the system is associated with increased job satisfaction and lowered turnover intention. Hospitals should implement a career ladder system and improve nurses' perception by addressing the specific categories identified in this study.